THE COACHING AS AN INNOVATIVE TOOL FOR THE TRAINING OF PROFESSIONAL SKILLS - García, Emersson (Revista Arbitrada Formación Gerencial, 2024)
The article presents the importance of coaching for the formation of professional skills; To achieve this, the theories of authors such as: Colorado and Corcino (2015), Eslava (2016), García (2013), Mussico (2013), among others, were supported. The research was classified as descriptive, governed by a documentary design Arias (2006) Bernal (2000). In short, the coaching tool is more than a professional with business training and knowledge of help techniques that allows creating a space for dialogue between him and the businessman or manager, a space for reflection to improve. Therefore; It requires a coach (leader) who has skills towards personal and professional growth who has an ambitious and transcendent vision, and who, through his example, discipline, responsibility and commitment, guides the team towards its objectives, turning it into a reality, that is, he is a leader who promotes team unity, is simple, warm, empathetic, listens, observes without individual preferences and consolidates the relationship within the team to enhance the sum of individual talents.